2018
DOI: 10.1002/jcp.27907
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pathological mechanisms, and genetic basis of limb‐girdle muscular dystrophies: A review

Abstract: Limb‐girdle muscular dystrophies (LGMDs) are a highly heterogeneous group of neuromuscular disorders that are associated with weakness and wasting of muscles in legs and arms. Signs and symptoms may begin at any age and usually worsen by time. LGMDs are autosomal disorders with different types and their prevalence is not the same in different areas. New technologies such as next‐generation sequencing can accelerate their diagnosis. Several important pathological mechanisms that are involved in the pathology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 97 publications
2
65
0
Order By: Relevance
“…The minimum prevalence of AR‐LGMD and MMD cases in the Netherlands amounted to 14.4 × 10 −6 individuals which is similar to the prevalence in the United Kingdom and less than in Italy . In our study, we found similar frequencies of AR‐LGMD and MMD subtypes to what is reported in Eastern, Central and Southern Europe but differs from the United Kingdom and Denmark.…”
Section: Discussionsupporting
confidence: 83%
“…The minimum prevalence of AR‐LGMD and MMD cases in the Netherlands amounted to 14.4 × 10 −6 individuals which is similar to the prevalence in the United Kingdom and less than in Italy . In our study, we found similar frequencies of AR‐LGMD and MMD subtypes to what is reported in Eastern, Central and Southern Europe but differs from the United Kingdom and Denmark.…”
Section: Discussionsupporting
confidence: 83%
“…Dystrophin, alpha-dystroglycan and sarcoglycan play important roles in maintaining sarcolemma stability and muscle integrity as the dystrophinglycoprotein complex 2 . Pathogenic variants in causative genes of sarcoglycanopathy lead to loss-of-function effects in different members of the skeletal muscle sarcoglycan complex and cause LGMD 2C, 2D, 2E and 2F 10 . However, pathogenic variants in FKRP lead to glycosylation defects in alpha-dystroglycan 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic variants in causative genes of sarcoglycanopathy lead to loss-of-function effects in different members of the skeletal muscle sarcoglycan complex and cause LGMD 2C, 2D, 2E and 2F 10 . However, pathogenic variants in FKRP lead to glycosylation defects in alpha-dystroglycan 10 . Mechanisms in each disorder are different.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in collagen 6α led to severe Ulrich CMD or milder Bethlem myopathy [ 24 ]. MDs showed genetic heterogeneity by sharing different clinical manifestations with the mutations in different genes, such as nine known genes associated with Emery–Dreifuss muscular dystrophy [ 30 ] and twenty-six known genes associated with limb-girdle muscular dystrophy [ 31 ]. Due to overlapping clinical symptoms and the multiple possible genetic causes for MDs and CMDs, it is difficult to obtain an accurate diagnosis for patients [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%